Soil fertility management in suppor of food sercurity in Sub-Saharan Africa - Soil fertility management in suppor of food sercurity in Sub-Saharan Africa (FAO, 2001)
This book reviews issues related to land degradation, with focus on problems of soil fertility management in SSA. It highlights some successfull experiences in the region, constraints and possible solutions specific to the major agro-ecological zones and the importance of holistic and participatory approaches for soil productivity improvement. The need for action and collaborative efforts of all stakeholders, within the framework of ongoing initiatives are emphasized.